2013
DOI: 10.1504/ijbaaf.2013.058088
|View full text |Cite
|
Sign up to set email alerts
|

Finance, growth and fragility: the role of government

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. distinguish between the policy view that relates financial sector development to an array of necessary policies and institutions, the historic view that relates financial sector development to historic and cultural factors, and the politics view that explains financial sector development as the result of political conflicts and decisions. These three views of financial sector deepening imply a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 59 publications
2
15
0
1
Order By: Relevance
“…In India one study found that financial deepening has been more important than financial inclusion in reducing poverty via promoting entrepreneurship overall, and job creation in services in urban areas. Access to credit was found to help specifically the rural self-employed (Beck, 2013). The regressions show that access to credit is not an important constraint for female (or male) participation in India.…”
Section: Access To Financementioning
confidence: 86%
“…In India one study found that financial deepening has been more important than financial inclusion in reducing poverty via promoting entrepreneurship overall, and job creation in services in urban areas. Access to credit was found to help specifically the rural self-employed (Beck, 2013). The regressions show that access to credit is not an important constraint for female (or male) participation in India.…”
Section: Access To Financementioning
confidence: 86%
“…The financial crisis of 2008 after the collapse of Lehmann Brothers created an unstable economic environment and exposed various regulatory framework inefficiencies worldwide (Beck, 2013). This in turn led to a domino effect that allowed the exposure of public debt issues affecting several European Union and Eurozone members, simultaneously raising the risk of default.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…It is important to note that this survey relies on previous work by the author on Africa (Beck et al, 2011), more general literature surveys on the relationship between economic and financial development (e.g. Beck, , 2013 as well as the recent Global Financial Development Report (World Bank, 2015), for which the author served as advisor and reviewer.…”
Section: Literature Surveymentioning
confidence: 99%